2018-2019 Florida Citrus Production Guide: Grove Planning and Establishment - Mongi Zekri; Ute Albrecht; Christopher Vincent (EDIS)
Many factors need to be considered when preparing for new tree plantings. Careful planning and preparation is necessary to ensure success and reduced frustrations in the future. Site selection, rootstock and scion selection, planting density, quality of trees, tree planting, irrigation, nutrition, and disease control are all important factors that contribute to success of new grove establishment. This 3-page fact sheet is part of the 2018-2019 Florida Citrus Production Guide. Written by Mongi Zekri, Ute Albrecht, and Christopher Vincent, and published by the Horticultural Sciences Department, May 2018.